(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In a nation where women are treated an equal to God, rape is a hatred crime perpetrated towards them. To be specific, it’s one of the most gruesome and heinous crime, that causes distress and agony not only to the victim and their kin but also to the society. According to NCRB Report, 2021, the total number of cases registered in India amounted to over 31,000. This number had been stirred up compared to the descending years